2015
DOI: 10.1021/acs.jpclett.5b01958
|View full text |Cite
|
Sign up to set email alerts
|

Optical Interference Enhances Nonlinear Spectroscopic Sensitivity: When Light Gives You Lemons, Model Lemonade

Abstract: Optical interference effects can be a nuisance in spectroscopy, especially in nonlinear experiments in which multiple incoming and outgoing beams are present. Vibrational sum frequency generation is particularly susceptible to interference effects because it is often applied to planar, layered materials, driving many of its practitioners to great lengths to avoid signal generation from multiple interfaces. In this perspective, we take a positive view of this metaphorical "lemon" and demonstrate how optical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 106 publications
1
10
0
Order By: Relevance
“…The nonresonant background term can be obtained from SFG spectral fitting, and in this case, it is negligible. Previous studies have shown that SFG signal has a strong dependence on the interference of light caused by different thicknesses of the object film, and in this case, the Fresnel coefficients of different interfaces in the above equations can be calculated using a three-layer interference model. , The Fresnel coefficients are also dependent on the PT film thickness (the thickness is embedded in the phase term of eq ). To deconvolute χ yyz interfaceI and χ yyz interfaceII from the overall collected SFG signal intensity, we need two I SFG measurements from films of two different thicknesses.…”
Section: Sfg Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The nonresonant background term can be obtained from SFG spectral fitting, and in this case, it is negligible. Previous studies have shown that SFG signal has a strong dependence on the interference of light caused by different thicknesses of the object film, and in this case, the Fresnel coefficients of different interfaces in the above equations can be calculated using a three-layer interference model. , The Fresnel coefficients are also dependent on the PT film thickness (the thickness is embedded in the phase term of eq ). To deconvolute χ yyz interfaceI and χ yyz interfaceII from the overall collected SFG signal intensity, we need two I SFG measurements from films of two different thicknesses.…”
Section: Sfg Theorymentioning
confidence: 99%
“…Combining the measured SFG signals of the PT layers with two different thicknesses with calculated Fresnel coefficients of the two interfaces for each sample, we can deduce the χ yyz interfaceI and χ yyz interfaceII and furthermore reconstruct the SFG spectra originating from each layer, which will be shown in the presented results below. The film thicknesses of the PT layers in this study were carefully chosen to be 60 and 100 nm. ,, …”
Section: Sfg Theorymentioning
confidence: 99%
“…212 In addition to the SFG studies on interfacial structures of semiconducting polymer thin films deposited on different substrates, SFG has also been applied to study semiconducting polymer films prepared with various methods. The annealing process of the spin-cast polymer film was found to affect the molecular structures of organic semiconductors at the interfaces, both p-type and n-type, reported by Anglin et al, 213 Kearns et al, 214 and Dhar et al 202 It was also found that, for semiconducting polymer films deposited using spin coating, different solvent combinations used to make the polymer solutions also impacted the structures of the buried polymer/ substrate interface. As reported by Xiao et al, 215 introducing a highly volatile solvent (acetone) into chlorobenzene (a widely used solvent to make the P3HT solution for spin coating) will cause the thiophene backbone to lie down on both the surface and interface (Figure 9c).…”
Section: (11f)mentioning
confidence: 82%
“…Kearns et al showed that ignoring the interference effect of the beam inside the target organic semiconductor thin film can significantly affect the interpretation and understanding of the data. 214 In addition to the SFG studies on the semiconducting polymer/dielectric interfaces, studies on the interfaces between organic semiconducting polymers and water or metal have also been reported recently. 216,217 In addition to the SFG studies on OFET based systems, SFG has also been applied to study other interesting systems.…”
Section: (11f)mentioning
confidence: 99%
“…146 The optical interference in SFG-VS, considering multiple interfaces in OFET, has the potential to detect small frequency shifts in the spectra induced by the gate bias. 147 Lack of knowledge regarding the interference effect could lead to misinterpretation of the SFG-VS data. Besides SFG-VS, electronic SFG has also been utilized to investigate the electronic structures of organic semiconductors such as P3HT.…”
Section: Semiconducting Polymersmentioning
confidence: 99%